Pulse modulation for attitude control with thrusters subject to switching restrictions - Kienitz, Karl Heinz; Bals, Johann (Aerospace science and technology, 2005)
A pulse modulation scheme based on two modulation curves is proposed for applications in spacecraft attitude control using thrusters which may be subject to switching restrictions. These constraints are taken into account explicitly during the design of the modulation scheme which can implement arbitrary bounded functions between constant modulator input and averaged modulator output.